Epidemiology of match injuries in Scottish professional rugby union - Bailey, S.; Martindale, R.; Engebretsen, L.; Robson, J.; Palmer, D. (British Journal of Sports Medicine, 2021)
Background Injury incidence in professional rugby union tends to be greater than other team sports. Epidemiological studies are required to describe injury occurrence and inform injury prevention measures. Objective To analyse injuries sustained by professional rugby union players in Scotland. Design Prospective observational. Setting Time-loss match injuries sustained in men's and women's international rugby, men's professional club rugby and men's and women's international sevens during the 2017/18 and 2018/19 seasons were recorded by Scottish Rugby medical staff. Match exposure was recorded by GPS device and/or video analysis. Patients (or Participants) Across all cohorts, 208 players (men: 163; women: 45) participated during the 2017/18 and 2018/ 19 seasons (men's international n = 60; women's international n = 37; men's professional club n = 134; men's international sevens n = 29; women's international sevens n = 25). Several players represented multiple cohorts. Interventions (or assessment of Risk Factors) Injuries within and between cohorts were compared. Main Outcome Measures Injury incidence, severity, type and location. Results Injury incidences were 292.8 (95% CI: 227.8-358.0)/ 1000 player match hours for men's international sevens, 183.3 (139.5-227.1)/1000 hours for women's international rugby, 167.5 (81.1-254.1)/1000 hours for women's international sevens, 160.0 (124.1-195.9)/1000 hours for men's international rugby, and 154.5 (140.2-168.8)/1000 hours for men's professional club. Median severity ranged from 6.0 - 19.5 days. Concussion (men's international: 22.5/1000 hours; women's international: 26.7/1000 hours; men's professional club: 28.9/1000 hours; men's international sevens: 37.3/1000 hours) was the most common injury for all cohorts except women's international sevens, where knee sprain/ligament injury was most frequent (41.9/1000 hours). Conclusions Men's international sevens had the greatest injury incidence. Concussion was the most frequent injury in all cohorts except women's international sevens, where it was the second most common. Interventions to reduce concussion incidence would benefit all professional cohorts in Scotland.